Petrographic and mineralogical study of ophioliteic ultramafic rocks in Bait jawiish – Balloran in Al Bassit area: in north - west of Syria. (Latakia University Journal -Basic Sciences Series, 2019)
The Petrographic study by polarized microscope  and mineralogical  study by scanning electron microscope for some samples of ophiolite ultramafic rocks in Bait Jawiish – Balloran in Al Bassit area have shown the diversity of Petrographic kinds of rocks, are  Dunite and two kinds of Peridotite (Harzburgite,Wehrlite), the dominout kind of olivine was forsterite, while the dominout kind of orthopyroxene was Hypersthene and that of clinopyroxene were Augite, Diopside, Diopside-  Enstatite.